Intervensi Konseling REBT terhadap Pelaku LGBT di Provinsi Banten - Ikhsan, Muhamad; Riswanto, Dody (Attractive : Innovative Education Journal, 2022)
The purpose of this study was to conduct REBT counseling interventions for LGBT actors. REBT counseling intervention was carried out through the A-B-C-D technique with the procedure of changing respondents from irrational beliefs to rational beliefs. The method used is a qualitative approach. Data collection techniques used are interviews, observations, documentation studies, and audio-visual information. Data analysis through data triangulation techniques, synthesizing, analyzing, interpreting data, and making conclusions in the final narrative in the form of propositions. The conclusions of the study were that the REBT counseling intervention resulted in behavioral changes, namely 1) respondents asked to be guided gently, not harshly, verbally, or bullying; 2) respondents improve the quality of their worship by regularly participating in spiritual activities, respondents become more religious as a result of the painful events they experience; 3) respondents try to reduce sexual activity with same-sex, in general respondents are still in a romantic relationship, but romance by not engaging in sexual relations anymore, respondents trying to reduce the intensity of sexual contact.